Modulation of clinical expression of plaque-induced gingivitis: response in aggressive periodontitis subjects - Leonardo Trombelli (Blackwell Synergy, 2006)
Aim: The aim of this study was to characterize the gingival inflammatory response to de novo plaque accumulation in subjects treated for aggressive periodontitis (AP). The gingival inflammatory response of the AP subjects was retrospectively compared with that of periodontally healthy individuals (PH) matched for exposure to plaque and of periodontally healthy subjects previously identified as ‘‘high responders’’ (HR) and ‘‘low responders’’ (LR). Materials and Methods: 13 AP subjects and 26 matched PH subjects participated in a 21-day experimental gingivitis trial. Plaque index (PlI), Gingival index (GI), gingival crevicular fluid volume (GCF) and angulated bleeding score (AngBS) were recorded at days 0, 7, 14 and 21. Cumulative plaque exposure (CPE), i.e. PlI over time, was also calculated. Results: GCF was significantly higher in AP compared with PH group at each observation interval (p40.001). In addition, GCF was significantly higher in AP group compared with either LR or HR groups at each observation interval (po0.001). Conclusions: These results suggest that susceptibility to gingival inflammation in response to de novo plaque accumulation may be related to susceptibility to periodontitis.